Environmental pressures on stomatal size may drive plant genome size evolution: evidence from a natural experiment with Cape geophytes - Veselý, Pavel; Šmarda, Petr; Bureš, Petr; Stirton, Charles; Muasya, A Muthama; Mucina, Ladislav; Horová, Lucie; Veselá, Kristýna; Šilerová, Alexandra; Šmerda, Jakub; Knápek, Ondřej (Annals of botany, 2020)
BACKGROUND AND AIMS: The idea that genome (size) evolution in eukaryotes could be driven by environmental factors is still vigorously debated. In extant plants, genome size correlates positively with stomatal size, leading to the idea that conditions enabling the existence of large stomata in fossil plants also supported growth of their genome size. We test this inductive assumption in drought-adapted, prostrate-leaved Cape (South Africa) geophytes where, compared with their upright-leaved geophytic ancestors, stomata develop in a favourably humid microclimate formed underneath their leaves. METHODS: Stomatal parameters (leaf cuticle imprints) and genome size (flow cytometry) were measured in 16 closely related geophytic species pairs from seven plant families. In each pair, representing a different genus, we contrasted a prostrate-leaved species with its upright-leaved phylogenetic relative, the latter whose stomata are exposed to the ambient arid climate. KEY RESULTS: Except for one, all prostrate-leaves species had larger stomata, and in 13 of 16 pairs they also had larger genomes than their upright-leaved relatives. Stomatal density and theoretical maximum conductance were less in prostrate-leaved species with small guard cells (<1 pL) but showed no systematic difference in species pairs with larger guard cells (>1 pL). Giant stomata were observed in the prostrate-leaved Satyrium bicorne (89-137 µm long), despite its relatively small genome (2C = 9 Gbp). CONCLUSIONS: Our results imply that climate, through selection on stomatal size, might be able to drive genome size evolution in plants. The data support the idea that plants from 'greenhouse' geological periods with large stomata might have generally had larger genome sizes when compared with extant plants, though this might not have been solely due to higher atmospheric CO2 in these periods but could also have been due to humid conditions prevailing at fossil deposit sites.
Keywords: Jihoafrická republika; listy rostlin; Genome Size; flow cytometry; fossil plants; stomatal size; délka genomu; Genome, Plant; genom rostlinný; South Africa; fylogeneze; Phylogeny; paleoclimate; Plant Stomata; Cape Floristic Region; genome size evolution; průduchy rostlin; Plant Leaves; carbon dioxide; geophyte